2012
DOI: 10.2169/internalmedicine.51.6347
|View full text |Cite
|
Sign up to set email alerts
|

Prehypertension in Children and Adolescents: Association with Body Weight and Neck Circumference

Abstract: Objective The present study was undertaken to investigate the role of neck circumference (NC) in predicting prehypertension in children and adolescents. Methods We conducted a cross-sectional study including 6,802 children and adolescents (3,631 boys and 3,171 girls) aged 5-18 years. Main anthropometric data and related information were collected. Results The prevalence of prehypertension was 14.4%, 16.4% and 17.1% in normal weight, overweight and obese group respectively. Among the participants with normal bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 35 publications
3
30
0
4
Order By: Relevance
“…The cutoff points described in this study should therefore be used with caution, as NC is a proxy for upper-body subcutaneous fat. 11 Furthermore, the moderate correlations and low specificity observed in the present study may be a consequence of the rapid growth and development that occurs during early years. Third, the cross-sectional nature of the data does not allow conclusions relating to causality.…”
Section: Neck Circumference To Identify Excess Body Weight In Childrementioning
confidence: 55%
See 1 more Smart Citation
“…The cutoff points described in this study should therefore be used with caution, as NC is a proxy for upper-body subcutaneous fat. 11 Furthermore, the moderate correlations and low specificity observed in the present study may be a consequence of the rapid growth and development that occurs during early years. Third, the cross-sectional nature of the data does not allow conclusions relating to causality.…”
Section: Neck Circumference To Identify Excess Body Weight In Childrementioning
confidence: 55%
“…In addition to obesity, 13 NC measurements have been shown to be suitable for assessing other risk factors in adults and children, including metabolic syndrome, 10,26 obstructive sleep apnea, 16 perioperative adverse respiratory events, 13 and cardio-metabolic risk factors. 9,11,14 Furthermore, in addition to its accuracy in identifying excess body weight and risk of other related health outcomes, La Berge et al 27 have reported that NC showed good inter-and intra-rater reliability and that it does not require multiple measurements for precision and reliability. The technique can also easily be learned by community caregivers and is simple to apply in general practice and epidemiological studies.…”
Section: Neck Circumference To Identify Excess Body Weight In Childrementioning
confidence: 99%
“…Guo et al [23] found that measurement of neck circumference might improve identification of prehypertension in normal weight children and adolescents beyond BMI. Kurtoglu et al [24] found that neck circumference was associated with blood pressure in Turkey obese children.…”
Section: Resultsmentioning
confidence: 99%
“…To date, a relatively large number of studies have been conducted to examine the associations between NC and varying health indicators in children (i.e., cardiovascular risk factors [2426], prehypertension [27], and perioperative adverse respiratory events [28]). However, a limited body of scientific evidence has been established to determine whether or not NC measurement can serve as a useful tool for classifying childhood overweight/obesity.…”
Section: Discussionmentioning
confidence: 99%